The use of a Laser Tracker and a Self-centring Probe for Rotary Axis Verification. (2015) - Acosta, D.; Albajez, J.A.; Velázquez, J.
Abstract: This paper presents a small collection of tests related with the analysis of a rotary axis according to ISO 230-7 but introducing two alternative equipments briefly explaining each method. The disadvantages of the methods in which the movement of a rotary axis engages the translational axes of a Machine Tool are expressed, which leads to the proposed study. The errors of a rotary axis are described as established in standards and the measurement procedures carried out in the tests for verification of a rotary indexing table, based on the use of a self-centring probe and a laser tracker, are explained. Also, the necessary elements setup for measurement are described. Then, the followed calculation process of the measured errors is explained in detail. Finally, the results of the most significant errors obtained from the test measurements are presented.